Impact of Laser Fluence on the Formation of T-Nb2O5 Nanostructure: A Study in a Liquid Environment - Evan T. Salim; Tamara E Abdulrahman; Raed Khalid Ibrahim; Zaid T. Salim; Rana O. Mahdi; Ahmed A. Al-Amiery; Subash C. B. Gopinath (International Journal of Nanoelectronics and Materials (IJNeaM), 2025)
In this work, different laser fluencies ranges (8.1–17.8 J/cm2) and Nd: YAG of 1064 nm wavelength were studied and analyzed. Energy band gaps acquired ranged from 4.2 eV to 3.9 eV. X-ray diffraction (XRD) results revealed the formation of an orthorhombic (T-Nb2O5) niobium pentoxide nanostructure. The grain size of the Nb2O5 nanoparticles ranged from approximately 58.2 nm to 244.6 nm. TEM images showed spherical particles whose density increased with increasing laser fluence. Raman and Fourier-transform infrared (FTIR) spectra exhibited peaks indicating the formation of T phase-Nb2O5 nanomaterial.